2016
DOI: 10.1055/s-0036-1595819
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastasis of a Primary Testicular Pure Choriocarcinoma Presenting with Frontal Lobe Hemorrhage

Abstract: We present the case of a 21-year-old male patient who was diagnosed with metastatic brain choriocarcinoma after presenting with a spontaneous cerebral hemorrhage. The treatment performed for this patient was an open surgery with full excision of the lesion. It is known that this kind of tumor is usually found in women, with low incidence in men. With this information as a baseline, we found multiple pulmonary metastases and a primary pure choriocarcinoma in his testicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…tumoral infiltration of the wall of a preexisting benign cavity and rupture into the pleural space. [11,12] It is believed that this case is significant as choriocarcinoma is a germ cell tumour that usually affects pregnant women and uncommonly occurs in men [13]. However, this study has reported a male case choriocarcinoma.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…tumoral infiltration of the wall of a preexisting benign cavity and rupture into the pleural space. [11,12] It is believed that this case is significant as choriocarcinoma is a germ cell tumour that usually affects pregnant women and uncommonly occurs in men [13]. However, this study has reported a male case choriocarcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…When this kind of tumour is diagnosed early, it responds well to chemotherapy. However, we must know that one of the most critical features of choriocarcinoma as an aggressive malignancy is its late diagnosis because its symptoms are mostly caused by metastatic lesions [13]. Therefore, it is utterly remarkable to know even the rarest manifestations of this tumour, to save the patient's life.…”
Section: Discussionmentioning
confidence: 99%